1994
DOI: 10.1016/0003-9969(94)90014-0
|View full text |Cite
|
Sign up to set email alerts
|

The time-course of the induction of reparative dentine formation in monkeys by recombinant human osteogenic protein-1

Abstract: Recombinant human osteogenic protein-1 (hOP-1, BMP-7) induces cartilage and bone formation when implanted in extra- and intraskeletal sites in vivo. rOP-1 also preserves pulp vitality and stimulates reparative dentine formation when placed on partially amputated vital dental pulp tissue. The amount of dentine formed in 6 weeks was earlier found to be proportional to the total amount of rOP-1/carrier placed on the pulp and the capacity of the pulp to respond to rOP-1 appeared to be independent of the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 7 publications
3
90
0
3
Order By: Relevance
“…BMPs have actions beyond bone in neural, renal and cardiac development. 1,2 BMPs also play a role in differentiation of dentin [3][4][5][6][7][8] in teeth. The recent progress in molecular developmental biology permits the delivery of BMPs by gene therapy using optimal delivery.…”
mentioning
confidence: 99%
“…BMPs have actions beyond bone in neural, renal and cardiac development. 1,2 BMPs also play a role in differentiation of dentin [3][4][5][6][7][8] in teeth. The recent progress in molecular developmental biology permits the delivery of BMPs by gene therapy using optimal delivery.…”
mentioning
confidence: 99%
“…However, chronic inflammation and a lack of pulp healing were observed, with no dentin bridge formation. It was later reported that eugenol is highly toxic, and zinc oxide eugenol resulted in high interfacial leakage [19][20][21][22] . In the 1970s, glucocorticoids combined with antibiotics were frequently used in an attempt to control pulpal pain and suppress pulpal inflammation 19,20,23) .…”
Section: Brief History Of Direct Pulp-capping Materialsmentioning
confidence: 99%
“…92 bağ dokusunun daha sonra mineralize olarak oluş turduğu tamir dentinin, pulpa dokusuna yüzeyel olarak şekillendiği ve derin pulpa dokusunu harcamaksızın pulpanın sağlıklı bir şekilde korunmasını sağladığı gösterilmiştir. 96 TGF-beta ailesi üyelerinden olan Bone Morphgenic Protein'lerden BMP-2, BMP-4 ve BMP-7 (OP-1) gibi proteinlerin de osteodentin ve ardından tübüler tamir dentin formasyonunu indüklediği bildirilmiştir. 97 Büyüme faktörleri ailesi -İnsülin benzeri büyü-me faktörleri‖ (IGF) üyelerinden IGF-I ile gerçekleş-tirilen pulpa kaplaması deneylerinde; pulpa ekspozunu tam olarak kapatan bir dentin köprüsünün ve arada tübüler tamir dentin formasyonunun oluştuğu gösterilmiştir.…”
Section: Biodentin(septodont Saint Maur Des Fossés France)unclassified